Digitalization of Hajj Fund Management through Shariah E-Commerce Model in the Context of Service and Global Investment Transformation - M. Dawud Arif Khan; Asqolani Asqolani; Maryadi Maryadi; Nur Aisyah Kustiani; Rifat Annur; Saepullah Saepullah (UIN Sunan Gunung Djati, 2025)
This study aims to analyze how the digitalization of hajj fund management can enhance efficiency, transparency, and accountability in accordance with Shariah principles. The urgency of this research lies in the increasing complexity of hajj services, which demand transparency, accessibility, and strong public accountability alongside the rapid development of digital technology. A qualitative approach was employed with literature review as the primary source of data. The analysis applied thematic analysis to identify recurring patterns and interactive qualitative analysis (IQA) to map the interrelationships among variables in the hajj management ecosystem. The reviewed literature covered government regulations, BPKH financial reports, academic studies on digital Islamic finance, as well as research on e-commerce platforms and Islamic fintech. The findings indicate that digitalization through Shariah-compliant Consumer-to-Consumer (C2C) models, integration with the Nusuk application, and collaboration with both domestic and international digital platforms improves cost efficiency, expands pilgrims’ access, and strengthens transparency in hajj fund governance. In addition, direct investment strategies in Saudi Arabia through government-to-government (G-to-G) and business-to-business (B-to-B) cooperation can minimize financial risks while diversifying revenue streams. The implications of this study affirm that digitalization is not merely a technical tool but a structural transformation strategy that has the potential to expand Islamic financial inclusion, strengthen the competitiveness of the hajj–umrah industry, and support the global growth of the Islamic economy. The originality of this research lies in its focus on the intersection of Shariah-based digital innovation—particularly the C2C e-commerce model—and hajj fund governance. This area remains underexplored in previous studies, thus providing novel contributions both theoretically to the development of digital Islamic finance studies and practically to policymaking in hajj fund management in Indonesia.